Nematode Behaviour 2004
DOI: 10.1079/9780851998183.0197
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical basis of behaviour.

Abstract: This paper discusses the physiological and biochemical (including some molecular) aspects of the behavioural responses of free living and plant parasitic nematodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Wong and Mai [70] reported that differences in root weight may be explained by gall development, gall mass being heavier than an equivalent linear length of similar non-galled roots. Perry et al [71] reported similar results that root weight increased in untreated infected plants compared with those amended with herbal powder due to the formation of galls and giant cells.…”
Section: Fresh Root Weightsupporting
confidence: 67%
“…Wong and Mai [70] reported that differences in root weight may be explained by gall development, gall mass being heavier than an equivalent linear length of similar non-galled roots. Perry et al [71] reported similar results that root weight increased in untreated infected plants compared with those amended with herbal powder due to the formation of galls and giant cells.…”
Section: Fresh Root Weightsupporting
confidence: 67%
“…The neuromuscular system of D. immitis shows great potential as a drug target; nematodes have well-developed neuromuscular systems that control motility, navigation, feeding, mating and responses to environmental cues, which are essential for their survival, development and reproduction (White et al., 1986, Perry et al., 2004, Greenberg, 2014). Interference with any of these activities can paralyse, kill or stop reproduction in the parasite (Greenberg, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This potent nematicidal action observed in the hydroalcoholic extract could be due to the known potent nematicidal compounds present in it. Important metabolites are formic acid, toxic on nematodes exposed [ 24 ], and γ-aminobutyric acid, which can cause paralysis of nematode muscles [ 25 ]. Trigonelline, also identified in the extract, plays an important role in plant resistance to pathogen attack.…”
Section: Discussionmentioning
confidence: 99%